Young Men, Mental Health, and Technology: Implications for Service Design and Delivery in the Digital Age - Ellis, Louise A; Collin, Philippa; Davenport, Tracey A; Hurley, Patrick J; Burns, Jane M; Hickie, Ian B (JMIR Publications, 2012)
BackgroundYoung men are particularly vulnerable to suicide, drug, and alcohol problems and yet fail to seek appropriate help. An alternative or adjunct to face-to-face services has emerged with widespread uptake of the Internet and related communication technologies, yet very little evidence exists that examines the capacity of the Internet to engage young men and promote help seeking. ObjectiveTo explore young people's attitudes and behaviors in relation to mental health and technology use. The aim was to identify key gender differences to inform the development of online mental health interventions for young men. MethodsA cross-sectional online survey of 1038 young people (aged 16 to 24 years) was used. ResultsYoung men are more likely than young women to play computer games, access online video/music content, and visit online forums. More than half of young men and women reported that they sought help for a problem online, and the majority were satisfied with the help they received. Significant gender differences were identified in relation to how young people would respond to a friend in need, with young men being less likely than young women to confront the issue directly. ConclusionsOnline interventions for young men need to be action-oriented, informed by young men's views and everyday technology practices, and leverage the important role that peers play in the help-seeking process.